Development of an e-module in basic physics II integrated with the alquran based on a saintific approach - Chandra, Artha Nesa; Lizelwati, Novia (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
This research is motivated by students' need for teaching materials that can be used as a guide to study independently anywhere and at any time in the Basic Physics II course. One of the teaching materials that can be used is E-Module. It is hoped that the Basic Physics II E-Module can help students understand lecture material, reduce student confusion and boredom in studying the large amount of Basic Physics II material. This research aims to produce a Basic Physics II E-module integrated with the Al-Quran based on a scientific approach that is valid and practical. This development research uses the ADDIE development model which consists of the Analysis, Define, Design, Implementation and Evaluation stages. The research instrument is a product validation sheet which was validated by several experts in the fields of media, materials and interpretation. The instrument is a response questionnaire sheet to measure product practicality by students. Data analysis was carried out in the form of analysis of validation results and analysis of student responses as users. This analysis was carried out descriptively. The data obtained from the questionnaire is tabulated and presented in tabular form, then the percentage is searched according to the formula, then the results of this percentage are compared with each value with the validity and practicality categories. Based on the results of data analysis, the average validity of the E-module according to material experts, media experts and interpretation experts was respectively 83%, 94% and 91.67% in the very valid category. The results of the student practicality questionnaire analysis were worth 84.48% in the very practical category. Thus, the E-module developed can be used as teaching material in Basic Physics II lecture activities.